Exploring Indonesian EFL Teachers’ Agency and Self-Efficacy in Using Artificial Intelligence Tools - Afreilyanti, Elizabet; Kuswandono, Paulus (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Despite numerous studies on teacher’s agency and self-efficacy, little attention has been given to examining how teachers’ agency manifests in the use of artificial intelligence and how it influences teachers’ self-efficacy. Teachers as active agents are demanded to effectively and independently exercise their digital agency in teaching. In essence, teacher’s agency allows them to make informed choices about using artificial intelligence to promote their teaching, which might influence their perceptions of their self-efficacy. Thus, this study aims to fill the gap by examining how EFL teachers’ agency manifests in the utilization of AI tools and how they perceive their self-efficacy. Employing a qualitative study, this research employed open-ended questionnaires and semi-structured interviews to gather the data. Five EFL teachers who have used artificial intelligence in their teaching participated in this study. To analyze the data, the researcher employed selective coding. The data revealed two teacher agency drove three participants to use artificial intelligence in three parts namely lesson planning, implementation, and assessment, and the other two participants used it for lesson planning and assessment. Furthermore, this study found that the five participants perceived high self-efficacy towards their use of artificial intelligence. Thus, schools and teacher educational programs should provide targeted professional development programs that emphasize the importance of teacher agency. In particular, training should focus on how teachers can utilize artificial intelligence tools to enhance their pedagogical practices that contribute to building high self-efficacy.